The impact of board characteristics on the effectiveness of internal control information disclosure——evidence from China-listed companies - Shi, Hao-Wei (2020)
For a long time, internal control is a hot research topic in the theoretical and practical fields. However, there are few empirical studies on the disclosure of internal control information of Listed Companies in China. The factors that affect the quality of internal control information disclosure of Listed Companies in China have not been fully studied and verified. Therefore, on the basis of previous studies, this dissertation discusses the relationship between the board characteristics and the effectiveness of internal control information disclosure (ICID).